2002
DOI: 10.1038/sj.bjp.0704789
|View full text |Cite
|
Sign up to set email alerts
|

P2Y1 and P2Y2 receptors are coupled to the NO/cGMP pathway to vasodilate the rat arterial mesenteric bed

Abstract: 1 To assess the role of nucleotide receptors in endothelial-smooth muscle signalling, changes in perfusion pressure of the rat arterial mesenteric bed, the luminal output of nitric oxide (NO) and guanosine 3',5' cyclic monophosphate (cGMP) accumulation were measured after the perfusion of nucleotides. 2 The rank order of potency of ATP and analogues in causing relaxation of precontracted mesenteries was: 2-MeSADP=2-MeSATP4ADP4ATP=UDP=UTP4adenosine. The vasodilatation was coupled to a concentration ± dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 47 publications
8
96
0
1
Order By: Relevance
“…The relaxant effects of ATP may be mediated by P2Y receptor subtypes in addition to P2X receptor subtypes. Buvinic et al [34] reported that P2Y 1 and P2Y 2 receptors are coupled to the NO/cGMP pathway. However, in our study, the contractile effects of P2X receptor subtypes are dominant over P2Y receptor effects on ATP, suggesting that the majority of relaxant effects of ATP in VD are mediated by P2X receptors.…”
Section: αβ-Meatp-induced Contractile Responses Of Vdmentioning
confidence: 99%
“…The relaxant effects of ATP may be mediated by P2Y receptor subtypes in addition to P2X receptor subtypes. Buvinic et al [34] reported that P2Y 1 and P2Y 2 receptors are coupled to the NO/cGMP pathway. However, in our study, the contractile effects of P2X receptor subtypes are dominant over P2Y receptor effects on ATP, suggesting that the majority of relaxant effects of ATP in VD are mediated by P2X receptors.…”
Section: αβ-Meatp-induced Contractile Responses Of Vdmentioning
confidence: 99%
“…In general, P2Y receptors are found both on vascular endothelial and smooth muscle cells [40,138]. RT-PCR studies found mRNA fragments for P2Y 1 , P2Y 2 and P2Y 6 receptors in the rat [21] and mouse [177] mesenteric arteries, while P2Y 4 mRNA wasn't detected [21]. Moreover, P2Y 1 -and P2Y 2 -immunoreactivity was present in the smooth muscle of the rat pancreatic vascular bed [29].…”
Section: P2x and P2y Receptors In The Splanchnic Circulationmentioning
confidence: 99%
“…This vasodilation is probably mediated by P2Y 1 and P2Y 2 receptors, through hyperpolarization of the endothelium that correlates with endothelium-dependent vasodilation [105]. This P2Y receptor-induced endotheliummediated vasodilation occurs through the release of NO, via the NO/cGMP pathway [21], and cyclo-oxigenase metabolites [97,105] but also via the release of EDHF [97,98,99,105,148]. In fact, EDHF-mediated vasodilation seems to be the predominant mediator of P2 receptor-mediated regulation of perfusion pressure in the small arteries of the peripheral circulation [96,172].…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that ATP activates P2X ligand-gated ion channels and G-protein coupled P2Y receptors, and that several subtypes of each family are present in endothelial cells (Marrelli, 2001;Buvinic et al, 2002;Ramirez and Kunze, 2002;Volonte et al, 2006), we tested the possibility that melatonin would discriminate between them. The agonists used, 2-methylthio ATP and a,b-methylene ATP, have been shown to stimulate NO-production in endothelial cells Melatonin inhibits NO production CLM Silva et al through P2Y 1 (Marrelli, 2001;Buvinic et al, 2002) and P2X 4 receptors (Burnstock, 2006;Yamamoto et al, 2006), respectively.…”
mentioning
confidence: 99%